Pleural empyema: Diagnosis of the situation in the Hospital de Clínicas - Salisbury, Siul; Chifflet, Juan (Cirugía del Uruguay, 1994)
The authors make a revision of pleural empyemas admitted to a general hospital in a period of 1 O years. lts frequency and incidence is established as compared to discharges from hospital in the same period. lnformation was obtained as regards approximate costs far the institution, and a/so as regards registry data, c/inical data, tests, medica/ and surgical treatment. The groups' mortality was a/so established and some proposals are made in arder to imporve the results obtained